PHOTOCHEMICAL UVC/H2O2 OXIDATION SYSTEM AS AN EFFECTIVE METHOD FOR THE DECOLOURISATION OF BIOTREATED PULP AND PAPER INDUSTRY WASTEWATER - Cappoani, Francieli Regina; Verona, Laís Bruna; Peri, Patrícia; Chaves Nogueira, Maria Rita; Soares, Petrick Anderson (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Biological oxidation processes have shown good results for the mineralisation of the non-recalcitrant fraction of wastewater from pulp and paper industry. However, they do not always represent a feasible technique for colour removal, requiring a polishing step for decolourisation before the wastewater discharged into a receiving water. In this study, photochemical UVC/H2O2 oxidation system was used as a polishing step in the decolourisation of a wastewater collected after biological oxidation from a pulp and paper industry. The photochemical oxidation assays were performed in a lab-scale photo-reactor whit a quartz tube (Ø = 20mm), filled on UVC lamp (6W), inside to inox tube (Ø = 70mm and L = 285mm). Photochemical reaction rates were determined under different operational conditions: H2O2 dosage (0 - 100 mM) and temperature (15°C , 25°C and 35°C). The results showing that the photochemical UVC/H2O2 oxidation system showed promising results as polishing step for the decolourisation of a bio-treated wastewater from pulp and paper industry. UVC and H2O2 alone showed negligible colour removal, indicating that the hydroxyl radicals generated from hydrogen peroxide photolysis under UVC radiation is the principal reaction mechanism. A higher hydrogen peroxide dosage and wastewater temperature showed a positive influence on the UVC/H2O2 system.